Effects of Leadership, Organizational Culture & Competence on Procurement of Government Goods and Services at the Directorate of Prevention and Control of Direct Communicable Diseases of the Indonesian Republic Ministry of Health - Surya Pujoyono; Bahrullah Akbar; Aries Djaenuri; Muh. Ilham (International Journal of Science and Society, 2019)
The research objective is to determine the effect of leadership on government procurement of goods and services, organizational culture of government procurement of goods and services, competence on government procurement of goods and services, leadership influence through organizational culture on government procurement of goods and services, leadership influence through competence on procurement of goods and government services, and formulate new concepts from the results of the discussion of the effects of leadership, organizational culture, and competence on the procurement of government goods and services. The research sample of 104 respondents was taken fully / fully. Data collection in this research uses a literature study, a research questionnaire, and observation. Data analysis using SEM Analysis. The results found that leadership influences Organizational Culture, Leadership influences Competence, Organizational Culture influences Government Procurement of Goods and Services, Competence influences Government Procurement of Goods and Services, and Leadership influences Government Procurement of Goods and Services.